Uji Validitas dan Reliabilitas Instrumen Penelitian Dukungan Suami terhadap Hambatan Penggunaan Metode Kontrasepsi Jangka Panjang pada Multipara Akseptor Aktif di Surabaya - Erina Krisnawati; Kurnia Dwi Artanti; Nurul Habibah Umar (Universitas Airlangga, 2024)
Background: Various factors motivate couples of childbearing age to use long-term contraceptive methods (MKJP), despite their effectiveness and efficiency being 20 times higher than non-MKJP types. One of them is the husband's support factor. Validity and reliability tests ensure that a research instrument for data collection complies with the rules. In validity testing, the test method often involves comparing the score of each statement item with the total score. Reliability testing often employs the Cronbach's alpha test. Objectives: This research aims to test the validity and reliability of the questionnaire with the variable husband's support on barriers to using MKJP among active multipara acceptors in Surabaya. Methods: This research was carried out with a quantitative analysis research design with the Great Surabaya Cadre analysis unit in Kenjeran District, which has active multipara acceptor status. Data were collected using convenience sampling from 30 Great Surabaya Cadres, Kenjeran District, by administering a questionnaire containing 10 statements about a husband's support with a measurement scale. Results: The results of the study stated that the husband's support questionnaire was valid and reliable, with a calculated Pearson r correlation value (0.469–0.748) > r table (0.361) and a Cronbach's alpha value of 0.809. Conclusion: Based on the results and discussion, a conclusion can be drawn, namely that the husband's support questionnaire regarding barriers to the use of MKJP among active multipara acceptors in Surabaya is declared valid and reliable.